Assessment of Robusta Coffee Quality Using Parameters of Specialty Coffee Association by Analytical Hierarchi Process (AHP) Method - Safrizal Safrizal; Yuliani Safmila; Miftahul Jannar; Yusmanizar Yusmanizar; Muhammad Idkham (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Understanding differences of the interests and tastes of each consumer are the basis for developing Robusta coffee in Aceh. This study aims to obtain consumer preferences on Robusta coffee in term of quality parameters of the Specialty Coffee Association (SCA). Robusta coffee samples were obtained from three places, namely Tangse, Lamno and Bener Meriah. Post-harvest handling of coffee beans included dry and wet processes. Preparation of test samples was carried out by following the SCA protocol, coffee testing was carried out by 3 professional panelists (Q-Grader). Consumer preferences was analyzed using the analytic hierarchical process (AHP) method. The results of the study indicated that the taste of Robusta coffee with a weight value 0.36 is preferred over other parameters. Based on the taste test on respondents, the best coffee based on ranking using the AHP method is Lamno coffee with wet processing which has a preference level of 0.0429. The results is in accordance with the cupping test assessment and the taste assessment which lies in the assessment of the best coffee, namely Lamno coffee with wet processing achieving a total cupping score of 75.25. Using the Analytical Heirarchy Process (AHP) method Lamno Robusta coffee with wet processing is the best based on the quality parameters from the SCA.   Keywords: AHP, Coffee, Lamno, Robusta, Tangse.